Myrina Kalaitzi. Figured Tombstones from Macedonia, Fifth–First Century BC. - Estrin, Seth (Journal of Greek Archaeology, 2019)
Myrina Kalaitzi dedicates this important new study of ancient Macedonian tombstones of the fifth through first centuries BC not to any named individual but to ‘the courageous reader.’ Most readers will not need courage to understand its familiar structure: a catalogue of surviving tombstones preceded by a chronological survey discussing major trends in the corpus. As Kalaitzi outlines in her Introduction, it is a structure determined less by a conceptual or theoretical model than by scholarly precedent – a structure that has been developed and deployed by scholars of ancient material culture on numerous occasions in order, ostensibly, to describe rather than interpret. The framework presumes that, when the corpus is addressed in comparative terms, visual patterns will emerge, ones that might tell us about cultural values shared between the people who produced or commissioned the individual monuments.